INDONESIAN PEPPER EXPORT COOPERATION TO INDIA IN 2017-2019 - Elsa Mulya Sarif; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study describes how the cooperation carried out by Indonesia and India in exporting pepper in 2017-2019. Indonesia cooperates with India in pepper exports, of which India is the main destination country for expanding the Indonesian pepper market. AIFTA (ASEAN-India Free Trade Agreement) which is a goods trade agreement, through AIFTA Indonesia and India are increasingly increasing cooperation covering goods, services and investment.The author collects data from books, academic journals, official documents, theses and sources from the internet related to research issues about. The author uses the perspective of liberalism and the level of analysis of the nation state. While the theory used in this theory is the theory of international cooperation.The results showed that pepper exports were carried out by Indonesia and India in 2017-2019, in this collaboration India provided an opportunity for Indonesia to expand the international pepper market because India has the potential for Indonesia to market its pepper.Keywords: Export, AIFTA, Cooperation, Pepper